The dark and bright side of laissez-faire leadership: Does subordinates’ goal orientation make a difference? - Zhang, Jiaojiao; Wang, Yao; Gao, Feng (Frontiers in Psychology, 2023)
Laissez-faire leadership is universally considered to be the most ineffective leadership style. However, a few recent researches revealed that laissez-faire leadership may have modest or even significant positive influence on subordinates’ work outcomes. To explain the inconsistent findings of laissez-faire leadership researches, the current study draws on stress theory and achievement goal theory to examine the boundary conditions and mechanisms underlying the impact of laissez-faire leadership on subordinate cognitive appraisal and subsequent performance. Results from an experience sampling study of 68 supervisor-subordinate dyads that completed daily surveys over ten consecutive work days indicated that: (1) when subordinate’s learning goal orientation is high, the relationship between laissez-faire leadership and hindrance appraisal will be positive; the indirect relationship between laissez-faire leadership and subordinate’s performance via subordinate’s hindrance appraisal will be negative; and (2) when subordinate’s performance-prove or performance-avoid goal orientation is high, the relationship between laissez-faire leadership and challenge appraisal will be positive; the indirect relationship between laissez-faire leadership and subordinate’s performance via subordinate’s challenge appraisal will be positive. This study found the double-edged sword effect of laissez-faire leadership at within-person level, which helps integrate inconsistent views in previous studies and explore the impact of laissez-faire leadership from a more nuanced and balanced perspective